Studi Penentuan State Of Charge (SOC) pada Baterai Valve Regulated Lead Acid NP7-12 Menggunakan MATLAB - Yenni Afrida; Jeckson J; Ubaidah U (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2023)
Abstract — To maintain battery performance, it is necessary to have a battery monitoring system that functions to determine several parameters in the battery, such as voltage, current, capacitance and battery capacity. The technology for knowing battery capacity is often known as state of charge (SOC). State of charge (SOC) is the ratio of the remaining energy to the maximum energy capacity of the battery. State of charge values ​​are often expressed in percentage form, 0 percent -100 percent. Estimating the value of the state of charge is quite important in battery monitoring technology. The lead acid battery testing process is carried out for 10 hours or 36000 seconds, both in the condition of discharging and charging the battery. In this study, the initial State of Charge (SOC) value for the battery is given, namely the upper limit and lower limit. The upper limit value for the initial State of Charge (SOC) is 100 percent, while the lower limit value is 20 percent. In the process of discharging the lead acid battery, it can be seen that the current value when discharging is stable at 1.2 Amperes. The charging current value is very constant, namely at 0.425 A. Meanwhile, the charging voltage value is also constant at 12.215 V. Keywords — State of Charge, Lead Acid, Coulomb Counting, Matlab.